2016
DOI: 10.1073/pnas.1604263113
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating monocytes promote brain inflammation and exacerbate neuronal damage after status epilepticus

Abstract: The generalized seizures of status epilepticus (SE) trigger a series of molecular and cellular events that produce cognitive deficits and can culminate in the development of epilepsy. Known early events include opening of the blood-brain barrier (BBB) and astrocytosis accompanied by activation of brain microglia. Whereas circulating monocytes do not infiltrate the healthy CNS, monocytes can enter the brain in response to injury and contribute to the immune response. We examined the cellular components of innat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
291
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(319 citation statements)
references
References 73 publications
14
291
1
1
Order By: Relevance
“…Interestingly, it was found that inhibiting the recruitment of monocytes, but not neutrophils, significantly reduced signs of neuroinflammation and cognitive impairment after infection . This is in line with numerous recent non‐IVM publications implicating monocytes in brain inflammation …”
Section: Systemic Infectionssupporting
confidence: 82%
“…Interestingly, it was found that inhibiting the recruitment of monocytes, but not neutrophils, significantly reduced signs of neuroinflammation and cognitive impairment after infection . This is in line with numerous recent non‐IVM publications implicating monocytes in brain inflammation …”
Section: Systemic Infectionssupporting
confidence: 82%
“…We investigated whether IN administration of A1-exosomes after SE would result in targeting of these exosomes into the hippocampus, the region exhibiting intense hyperactivity of neurons, increased oxidative stress, and inflammation with infiltration of peripheral monocytes during and/or after SE (5,12). We administered PKH26-labeled A1-exosomes via IN route (15 μg, ∼7.5 × 10 9 ) immediately after the termination of 2 h of SE by an injection of diazepam.…”
Section: In-dispensed A1-exosomes Incorporated Into Cortical and Hippmentioning
confidence: 99%
“…It can produce substantial neurodegeneration, blood-brain barrier disruption, and inflammation in the hippocampus if not extinguished quickly by antiepileptic drug (AED) treatment (3)(4)(5). An episode of extended SE is sufficient to cause chronic hippocampus dysfunction, exemplified by persistent inflammation with activation of microglia and monocyte infiltration, loss of sizable fractions of several subclasses of inhibitory interneurons, aberrant and waned neurogenesis, hippocampus-dependent cognitive and memory impairments, and chronic epilepsy (5)(6)(7)(8)(9)(10)(11)(12). Numerous situations such as head trauma, stroke, Alzheimer's disease, brain tumor, and encephalitis can engender SE.…”
mentioning
confidence: 99%
“…Recent studies, however, showed that in addition to resident microglia, infiltrating immune cells (i.e. , monocytes, leukocytes) invade the hippocampus after seizures and contribute significantly to pathogenesis (Tian et al, ; Varvel et al, ; Zattoni et al, ). In this study, we used complimentary techniques to investigate the source of microgliosis, particularly the respective contribution of monocyte infiltration and local proliferation in epilepsy.…”
Section: Introductionmentioning
confidence: 99%